Perfect little world - Wilson, Kevin, 1978- (Ecco, an imprint of HarperCollinsPublishers, 2017)
When Isabelle Poole meets Dr. Preston Grind, she's fresh out of high school, pregnant with her art teacher's baby, and totally on her own. Izzy knows she can be a good mother but without any money or relatives to help, she's left searching. Dr. Grind, an awkwardly charming child psychologist, has spent his life studying family, even after tragedy struck his own. Now, with the help of an eccentric billionaire, he has the chance to create a "perfect little world"--to study what would happen when ten children are raised collectively, without knowing who their biological parents are. He calls it the Infinite Family Project and he wants Izzy and her son to join. This attempt at a utopian ideal starts off promising, but soon the gentle equilibrium among the families disintegrates: unspoken resentments between the couples begin to fester; the project's funding becomes tenuous; and Izzy's growing feelings for Dr. Grind make her question her participation in this strange experiment in the first place. Written with the same compassion and charm that won over legions of readers with The Family Fang, Kevin Wilson shows us with grace and humor that the best families are the ones we make for ourselves.--Page [4] of dust jacket.